Study of day, month and season pedometer-determined variability of physical activity of high school pupils in the czech republic - Pelclová, Jana; Walid, El Ansari; Vašícková, Jana (Journal of sports science & medicine, 2010)
Long-term day-to-day monitoring of physical activity (PA) has not been undertaken in adolescents despite PA declines rapidly during adolescence. This study monitored the school year-round pedometer-determined PA of pupils attending high school in the Czech Republic. We assessed their PA levels; appraised the school year-round variability of their PA; and, assessed the associations between their PA levels and weekdays/weekends; months; seasons; and physical education (PE) lessons at school. We observed the PA levels of 10 girls and 2 boys (aged 16.0 ± 0.7 years). Each pupil wore an unsealed pedometer (Omron HJ-105) on the right side of the waist continuously for one year, and recorded steps/day and daily behaviour (e.g. after-school PA, PE lesson) into an activity diary. In total, participants recorded step counts for 2,979 person- days (82.0% of a possible 3,628 person-days). We used the Missing Values Analysis EM function of SPSS to estimate step values that were missing from the dataset. The sample's mean daily step count was 14,727 ± 6,612 steps/day, and repeated ANOVA showed differences in steps/day across the days of the week (p < 0.0001), months (p < 0.0001) and seasons (p < 0.0001). The mean number of steps/day for weekdays (15,733 ± 6,354) was higher (p < 0.0001) than weekends values (12,196 ± 6,574), and was higher for days with PE lesson (17,280 ± 5,988) than for days without PE lesson (15,569 ± 6,318) (p < 0.0001). The total contribution of PE class (90 minutes) to pupils' daily PA was 10.0% additional steps per PE day. In conclusion, this study contributes to understanding the day-to-day PA variability of adolescent pupils across the school year. Across all months and seasons, pupils achieved notably more steps on weekdays than on weekends; and on PE days than on non-PE days. Research is required to assess these findings for school pupils in other countries. Key pointsPedometer appears to be suitable for long-term monitoring of physical activity in adolescents.Day of the week, month and season are significant factors in pedometer-determined day-to-day variability of physical activity of adolescent pupils.Across all months and seasons, pupils achieved notably more steps on weekdays than on weekends, with Sunday being the least active day.Regular PE lessons contribute considerably to the total physical activity levels in adolescent pupils. The increase in steps/day on days with PE is relatively constant throughout the school year regardless of month, season and the content of PE lessons.
Keywords: pedometer; school year; adolescents; Day-to-day variability; physical education